2017
DOI: 10.1002/jcc.24918
|View full text |Cite
|
Sign up to set email alerts
|

Revised CHARMM force field parameters for iron‐containing cofactors of photosystem II

Abstract: Photosystem II is a complex protein-cofactor machinery that splits water molecules into molecular oxygen, protons, and electrons. All-atom molecular dynamics simulations have the potential to contribute to our general understanding of how photosystem II works. To perform reliable all-atom simulations, we need accurate force field parameters for the cofactor molecules. We present here CHARMM bonded and non-bonded parameters for the iron-containing cofactors of photosystem II that include a six-coordinated heme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
0
23
0
1
Order By: Relevance
“…Currently, several all-atom and UA FFs are available and validated for all amino acids, several lipid classes, and different solvents (Oostenbrink et al 2004;Zhu et al 2012;Nerenberg and Head-Gordon 2018). Importantly for the photosynthetic community, nowadays several of these FFs have also been derived and validated for photosynthetic pigments and cofactors: most all-atom FFs (such as CHARMM and Amber) have been validated by comparing simulated properties against ab initio calculations (Damjanović et al 2002;Ceccarelli et al 2003;Karki and Roccatano 2011;Cerezo et al 2013;Guerra et al 2015;Adam et al 2018;Kim et al 2018). In the case of the Amber force field for Cars (Prandi et al 2016), this set of parameters has been specifically validated to reproduce selected spectral properties.…”
Section: Atomistic Force Fieldsmentioning
confidence: 99%
“…Currently, several all-atom and UA FFs are available and validated for all amino acids, several lipid classes, and different solvents (Oostenbrink et al 2004;Zhu et al 2012;Nerenberg and Head-Gordon 2018). Importantly for the photosynthetic community, nowadays several of these FFs have also been derived and validated for photosynthetic pigments and cofactors: most all-atom FFs (such as CHARMM and Amber) have been validated by comparing simulated properties against ab initio calculations (Damjanović et al 2002;Ceccarelli et al 2003;Karki and Roccatano 2011;Cerezo et al 2013;Guerra et al 2015;Adam et al 2018;Kim et al 2018). In the case of the Amber force field for Cars (Prandi et al 2016), this set of parameters has been specifically validated to reproduce selected spectral properties.…”
Section: Atomistic Force Fieldsmentioning
confidence: 99%
“… 41 Luthey-Schulten and coworkers optimized the partial charges and bonded parameters for the heme, hexacoordinated with ligands appropriate to Cyt c , relying on both protein X‐ray structures and ab initio density functional theory (DFT) geometry optimizations at the B3LYP/6‐31G* level. 42 Adam and coauthors have recently carried out a similar optimization of the standard CHARMM parameters, for the Photosystem II, 43 while Soloviov and coauthors added an ad hoc potential term to the CHARMM22 force field to model the ligand-heme interaction in Myoglobin–NO. 44…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The derived Fe 2+ metal charges in the [2FE-2S] cluster were reported to have positive values of 0.590 (FE 2 ) and 0.732 (FE 3 ), which is consistent with previous studies [ 63 ]. However, FE 1 in b-type heme bL was reported to have RESP charges of −0.009, unlike previous studies that reported the RESP charge for Fe 2+ to be 0.16 using the HF/6-31G* charge calculation method [ 64 ]. Additionally, other studies have reported a charge of 0.45 and 1.58 in a-type and c-type heme structures respectively [ 65 , 66 ].…”
Section: Resultsmentioning
confidence: 80%